Sources of variability in fed-cattle grid pricing - J.L. Graff; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1999)
Price variability among carcasses increases with a change from live-weight to dressedweight to grid pricing. Grid pricing has the largest price variability, because the price for each carcass is influenced by all of the components of the grid, rather than all cattle selling for the same live or dressed price. Therefore, producers selling on a grid need to have knowledge about the expected carcass merit of their cattle. We used data on 11,703 head of cattle to determine which grid pricing components influence price variability the most and to measure how much price variability increases from grid pricing, relative to live and dressed pricing, at the individual-carcass and individual pen levels. The Choice-to-Select price spread has the largest influence on price variability per hundredweight, and average carcass weight had the largest influence on price variability per head. Whether price variability increased for both individual-head and individual-pen levels depended on the quality of the cattle sold and the grid on which they are sold. To manage the increased price risk created by pricing, producers must first manage that risk on an individualhead level through genetics, management, and sorting methods. The more knowledge producers have about the expected merit of their cattle, the more profit can be enhanced through grid pricing.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Grid pricing; Value-based pricing; Price variability